Heterologous vaccination with subunit protein vaccine induces a superior neutralizing capacity against BA.4/5‐included SARS‐CoV‐2 variants than homologous vaccination of mRNA vaccine - Dandan Peng; Tingmei Zhao; Weiqi Hong; Minyang Fu; Cai He; Li Chen; Wenyan Ren; Hong Lei; Jingyun Yang; Aqu Alu; Yanghong Ni; Jian Liu; et al. (MedComm)
Abstract BA.4 and BA.5 (BA.4/5), the subvariants of Omicron, are more transmissible than BA.1 with more robust immune evasion capability because of its unique spike protein mutations. In light of such situation, the vaccination against severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) is in desperate need of the third booster. It has been reported that heterologous boosters might produce more effective immunity against wild‐type SARS‐CoV‐2 and the variants. Additionally, the third heterologous protein subunit booster should be considered potentially. In the present study, we prepared a Delta full‐length spike protein sequence‐based mRNA vaccine as the “priming” shot and developed a recombinant trimeric receptor‐binding domain (RBD) protein vaccine referred to as RBD–HR/trimer as a third heterologous booster. Compared to the homologous mRNA group, the heterologous group (RBD–HR/trimer vaccine primed with two mRNA vaccines) induced higher neutralizing antibody titers against BA.4/5‐included SARS‐CoV‐2 variants. In addition, heterologous vaccination exhibited stronger cellular immune response and long‐lasting memory response than the homologous mRNA vaccine. In conclusion, a third heterologous boosting with RBD–HR/trimer following two‐dose mRNA priming vaccination should be a superior strategy than a third homologous mRNA vaccine. The RBD–HR/trimer vaccine becomes an appropriate candidate for a booster immune injection.